ANNOTATION FEEDBACKIN EDMODO ONSTUDENTS' PROCEDURE TEXT : A Quasi-experimental at One College in Bandung, Indonesia - Hidayat, Fahmi (2015)
This study investigated the effect annotation feedback in Edmodo on students' procedure text in one college in Bandung, West java, Indonesia. The annotation feature in Edmodo used in this research was teacher indirect feedback as defines by Ellis (2008). The study aimed to provide evidence that the students gained more interest and confidence in writing by using technology. The study used quantitative approach employing a quasi-experimental design. The quasi-experimental design was carried out by using an Independent t-test design. The study involved 44 participants divided into two groups (Experimental and Control groups). The data were collected by using three types of instruments including pre-tests and post-test, assessment format, and questionnaire. Pre-tests and post-test were conducted for both the experimental and control groups; students were given the same instructions and scored by using the same scoring rubric. Students were asked to write a procedural text for at least one paragraph length. In order to assess students' text, the assessment format used in this study assessed the content, organization, vocabulary, language use, and mechanics of the texts. In the end of the program, the questionnaire was carried out after the post-test, asking students' attitude toward Edmodo. The study resulted in the following findings; (1) students in this study were successful in correcting their errors and improving their writings after the teacher gave annotation feedbacks for their pretest. However, their writings still need improvement since the same problems and even the new problems were still found in students' posttest. First, the students did not use correct words in describing their thought. Second, the students did not use correct verbs. Since the genre of the text was procedure, the students were required to use action verbs without any subject preceded. Third, the students did not use punctuation mostly at the end of their sentences. (2) The students had positive attitudes towards collaboration, sharing ideas, and maintaining relation via Edmodo in producing a text. Therefore, the students have motivation to write, easy to get ideas, and interested in improving the writing. Likewise, they feel comfortable in writing, know how to organize sentences or paragraphs, and provide the exposure in increasing vocabulary. Further, the study recommends that a study with applying various features of Edmodo and different types of feedback to improve students' writing. Keywords: Annotation feedback, Edmodo, procedure text